IInduction of G2/M Phase Block and Apoptosis by Kaempferol in Human Sarcoma Cells - Ishiki, Manabu; Yoshii, Miho; Kanamori, Masahiko (Indonesian Journal of Cancer, 2024)
malignant cells has interested us to seek new strategies for the treatment of sarcoma. Flavonoids have been recently claimed to exert anti-cancer effects. We focused on the flavonoid kaempferol, to determine whether it induces apoptosis of sarcoma cells in vitro. Methods: We examined cell growth using a CCK-8 assay, morphology, cell cycle analysis, and the apoptosis or differentiation effects of kaempferol on cultured human osteosarcoma MG-63 cells. All experiments were performed at least three times in duplicates. The ANOVA and independent sample t-test were used for the comparison of the continuous variables Results: Kaempferol (50 μM), adversely affected the proliferation of MG-63 cells. Anti-proliferative action of kaempferol appeared to be linked to apoptotic cell death based on the morphological changes depicting nuclear fragmentation. Cell cycle analysis demonstrated the induction of G2/M phase arrest and an enhanced sub-G1 population. However, the intracellular alkaline phosphatase (ALP) activity was observed to have been stimulated. This apoptosis might be associated with cell differentiation of the cells in the early stage. Conclusions: This study demonstrates that kaempferol inhibited the growth of MG-63 cells in vitro. G2/M phase arrest and induction of intracellular ALP activities in the early phase are observed. These findings indicate that kaempferol may present as an additional pharmacological tool for the treatment of human sarcoma cells.